Sustentabilidad Socio-Cultural y Buen Vivir en Sitios Patrimoniales: Evaluación del Caso Agua Blanca, Ecuador - Endere, Maria Luz (2015)
The incorporation of sustainability objectives as the focus of preservation of cultural heritage show a strong social concern in Ecuador, especially in the framework of the Buen Vivir (Good Living) Plan, proposed as a state policy. This paper examines the socio-cultural sustainability of the archaeological site Agua Blanca, a Community Tourism Center located at Manabi province, after defining a number of aspects needed to assess sustainability. Six main evaluation criteria were identified, which include 25 qualitative indicators. These may serve as an input to improve the management of heritage sites. The results reveal that the socio-cultural sustainability of the site, in this particular context, is high for 64% of the indicators considered. The involvement of the community of Agua Blanca in the configuration of the site is what mainly determines the high sustainability of its tangible and intangible heritage in line with the objectives of the Buen Vivir.